PENINGKATAN MOTIVASI BELAJAR MELALUI PENGGUNAAN MEDIA AUDIO VISUAL PADA MATA PELAJARAN SKI SISWA KLS VII G DI MTs Al MAARIF SINGOSARI - Endang Waleuru; Ika Ratih Sulistiani; Lia Nur Atiqoh Bela Dina (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This study aims to describe the implementation of audio visual learning media in increasing learning motivation in SKI subjects in class VII G Mts Al-arif 01 Singosari. and describe the results of the increased use of Audio Visual learning media in class VII G Mts Al-arif 01 Singosari. Data sources were obtained from the principal, teacher and several students. This study uses qualitative methods with two objects namely primary and secondary, documents obtained based on the results of interviews, observation and documentation. Furthermore, it is analyzed by arranging, sorting and grouping the code so that a finding is obtained based on the focus or problem that wants to be answered, so that it is reduced by a document and drawing conclusions and verifying conclusions. The results of this study indicate that audio-visual media methods can create students' interest in learning better. The existence of these things increases students' interest in learning, as well as higher learning motivation and difficult lessons that are easily understood and understood by students. The teacher motivates students so that in terms of learning to use audio-visual methods students who can learn more easily and can be understood.